2013
DOI: 10.5194/os-9-281-2013
|View full text |Cite
|
Sign up to set email alerts
|

Co-existence of wind seas and swells along the west coast of India during non-monsoon season

Abstract: Abstract. An attempt has been made to understand the coexistence of wind seas and swells along the west coast of India during non-monsoon season. Wave data were collected in different years during non-monsoon season (off Goa during May 2005, off Ratnagiri during January-February 2008 and off Dwarka during December 2007-January 2008), which is fairly a calm weather season along these regions. Diurnal variation in wave parameters is noticeable along the central west coast of India (off Goa and Ratnagiri), which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…During these events, there is a sharp increase in wave height that may exceed 3.5 m in the northwestern Arabian Sea and 1.0-2.0 m along the west coast of India. Although south swells from the Indian Ocean are always present along the west coast of India, Shamal events are the main contributor to the sea states [31].…”
Section: Case Study and Data Sourcesmentioning
confidence: 99%
“…During these events, there is a sharp increase in wave height that may exceed 3.5 m in the northwestern Arabian Sea and 1.0-2.0 m along the west coast of India. Although south swells from the Indian Ocean are always present along the west coast of India, Shamal events are the main contributor to the sea states [31].…”
Section: Case Study and Data Sourcesmentioning
confidence: 99%
“…Identification and separation of wind sea and swell energies from the measured spectra allow us to have a more realistic description of the sea state (Wang and Hwang, 2001). The wind sea and swell parameters can be separated using the methodology given by Gilhousen and Hervey (2001), which is based on the wave steepness algorithm (Rashmi et al, 2013). It is observed that during late premonsoon season, swells are dominant (54 % and 71 % at 25 m and 15 m water depths off Goa, respectively) ( Table 1).…”
Section: Dominance Of Wind Seas and Swellsmentioning
confidence: 99%
“…However, when wind seas dominate, mixed seas also increase as the waves are still in the developing stage. (Rashmi et al, 2013).…”
Section: Dominance Of Wind Seas and Swellsmentioning
confidence: 99%
“…Measured wave data in Chabahar bay in the northern coasts of Gulf of Oman are used to verify the proposed approach. The area is experiencing both wind-sea and swell regimes throughout the year especially in Monsoon seasons (Rashmi et al, 2013). As the border of Indian Ocean and Gulf of Oman, it is under construction and development activities and its field observations are recently released.…”
Section: Introductionmentioning
confidence: 99%